A framework for effective private dispute resolution in the Malaysian construction industry / Zulhabri Ismail - Ismail, Zulhabri (2010)
Private dispute resolution refers to settlement/resolution of disputes "other than litigation". This research aims to analyse the development and use of construction private dispute resolution in the Malaysian construction industry and would establish a framework for private dispute resolution. Literature review on the development of private dispute resolution in other countries indicated active utilisation. However, private dispute resolution in Malaysia is not develop at the same level. Mixed methods of quantitative and qualitative research were adopted to analyse the use of private dispute resolution. Empirical data for quantitative research was collected via cross sectional survey and qualitative data was gathered via indepth semi-structured interviews. Two hundred thirty one responses were received from G7 contractors in Malaysia and analysed by non-parametric statistical analyses. Quantitative analyses confirmed the use of private dispute resolution was still underutilised. The use of private dispute resolution did not correlate with years of establishment of the construction organisations, experience of individual respondents in the construction industry, value of contract price and project duration. Thus, general presumptions on the use of arbitration for larger amounts at stake and mediation for smaller disputes may not be conclusive. The reason for low utilisation of private dispute resolution was bad experience in the process. As a result, the disputants applied private dispute resolution between one and two times. Consistent with previous research, arbitration was the most unsatisfying and mediation/conciliation can be classified as considerably accepted and recommended. Those who experienced adversarial and non-adversarial dispute resolution tended to have preference over non adversarial dispute resolution. The three main reasons for dissatisfaction towards private dispute resolution in which the major impediment for active utilisation in the construction industry are: tedious and complicated process; dissatisfaction with third party dispute resolvers; and problems in record keeping, evidence and witnesses. Further qualitative research was conducted to investigate reasons for appropriateness and inappropriateness of private dispute resolution by looking into successful and unsuccessful stories behind the process. Appropriateness of private dispute resolution was very much dependant on the commitment and consistency of disputed parties; the relationship; amount disputed; experience in dispute resolution; and typical issues of time and cost were among the main problematic issues. This research indicated that the issue of bias is involved in determining the most appropriate method. In order to make private dispute resolution more effective, a framework to further utilise and improve private dispute resolution was proposed. The framework consists of: Criteria for appointment of a private dispute resolution practitioner, important elements in dispute resolution, factors to further utilise and improve; a mechanism for effective settlement of disputes; and a mechanism to further utilise and improve private dispute resolution by active participation of various parties.